2011
DOI: 10.1182/blood-2010-05-284869
|View full text |Cite
|
Sign up to set email alerts
|

Delta-like ligand 4–Notch signaling regulates bone marrow–derived pericyte/vascular smooth muscle cell formation

Abstract: Delta-like ligand 4 (DLL4) is essential for the formation of mature vasculature. However, the role of DLL4-Notch signaling in pericyte/vascular smooth muscle cell (vSMC) development is poorly understood. We sought to determine whether DLL4-Notch signaling is involved in pericyte/vSMC formation in vitro and during vasculogenesis in vivo using 2 Ewing sarcoma mouse models. Inhibition of DLL4 with the antibody YW152F inhibited pericyte/vSMC marker expression by bone marrow (BM) cells in vitro. Conversely, transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…Collectively, these data suggest a critical dosage sensitivity requirement for Notch signaling in angiogenesis and that perturbations in either direction are deleterious to the overall process. In keeping with our data, recent studies in Ewings sarcoma xenograft models report that blockade of Dll4 using either shRNA or a mouse cross-reactive antiDll4 antibody is associated with a decrease in pericyte/ VSMC coverage (13,35). Taken together, our findings are consistent with a role for Dll4-Notch signaling in pericyte/vSMC development and, in future studies, it will be interesting to further elucidate the role of Dll4 relative to other Notch pathway members (e.g., Notch3) in pericyte recruitment and vessel maturation.…”
Section: Discussionsupporting
confidence: 71%
“…Collectively, these data suggest a critical dosage sensitivity requirement for Notch signaling in angiogenesis and that perturbations in either direction are deleterious to the overall process. In keeping with our data, recent studies in Ewings sarcoma xenograft models report that blockade of Dll4 using either shRNA or a mouse cross-reactive antiDll4 antibody is associated with a decrease in pericyte/ VSMC coverage (13,35). Taken together, our findings are consistent with a role for Dll4-Notch signaling in pericyte/vSMC development and, in future studies, it will be interesting to further elucidate the role of Dll4 relative to other Notch pathway members (e.g., Notch3) in pericyte recruitment and vessel maturation.…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, it has been suggested that notch signalling can stabilise newly formed blood vessels by affecting pericytes. For example, pericyte marker expression in cells cultured from bone marrow increases with notch signalling (Stewart et al, 2011), and a recent study suggested that the stabilising effect of ANG1/TIE2 signalling between pericytes and ECs is mediated via induction of DLL4 expression in ECs (Fig. 5) (Zhang et al, 2011).…”
Section: Network Formation: Remodelling and Maturationmentioning
confidence: 99%
“…Other groups provided evidence of Dll4 enhancing pericyte coverage of tumor vessels, 29,30 and defective vessel maturation and perfusion is a result of Dll4 ablation. 31 Defective recruitment of pericytes, hyperproliverative angiogenesis, enhanced permeability, insufficient maturation and perfusion are all well-known aspects in CCM pathology and underline the relevance of Dll4-Notch3 signaling in this neurological entity.…”
Section: May 2015mentioning
confidence: 99%